1996
DOI: 10.1161/01.str.27.7.1192
|View full text |Cite
|
Sign up to set email alerts
|

Do Changes in Oxygen Metabolism in the Unaffected Cerebral Hemisphere Underlie Early Neurological Recovery After Stroke?

Abstract: We found no evidence for an influence of cCMRO2 on acute-stage neurological deficit or for a role of the unaffected hemisphere in early recovery after acute MCA ischemic stroke. The decline in unaffected-hemisphere metabolism from the acute to the subacute stage in the face of overall clinical recovery appears clinically irrelevant. The fact that the neocortical cCMRO2 at PET2 tended to be lower, and declined significantly from PET1 to PET2 in the mirror region in the subgroup of patients with large infarcts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…This is determined both by the extent of the local increase in blood flow after brain activation and the magnitude of the increase in the cerebral metabolic rate for oxygen consumption (CMRO 2 ). 10 In our study the patients and controls showed identical behavioral performance (in the sequential finger-tapping task), and there is no evidence for a hypermetabolic state with increased CMRO 2 in patients after ischemic stroke (in fact, more typically there are decreases 23,24 ). Differences in cerebral blood volume changes also could lead to differences in BOLD response, 10 but such changes are not expected to be generalized in patients with focal infacts.…”
Section: Discussionsupporting
confidence: 46%
“…This is determined both by the extent of the local increase in blood flow after brain activation and the magnitude of the increase in the cerebral metabolic rate for oxygen consumption (CMRO 2 ). 10 In our study the patients and controls showed identical behavioral performance (in the sequential finger-tapping task), and there is no evidence for a hypermetabolic state with increased CMRO 2 in patients after ischemic stroke (in fact, more typically there are decreases 23,24 ). Differences in cerebral blood volume changes also could lead to differences in BOLD response, 10 but such changes are not expected to be generalized in patients with focal infacts.…”
Section: Discussionsupporting
confidence: 46%
“…The loss of anisotropy associated with hemispheric atrophy contralateral to MCA infarcts strongly supports that secondary degeneration and demyelination spread to the contralateral hemisphere during the first 6 months after the occurrence of a MCA infarction. Only functional modifications have been previously reported in the contralateral hemisphere after MCA infarcts using SPECT (Bowler et al, 1995) or PET (Iglesias et al, 1996), the role of which in clinical recovery is now debated. Remarkably, a significant increase in FA was also detected in the hemisphere ispilateral to the ischemic lesion with histograms and a similar trend was found in the contralateral hemisphere at M3 before the final loss of anisotropy measured at M6.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in energy demands are unlikely because increase in oxygen consumption could be excluded in patients after stroke. 33 Because combined temporal changes in neural activity and cerebrovascular hemodynamics occur during recovery after brain lesion, appropriate evaluation of neural plastic changes remains challenging. In the present study, we have shown that CVR regional heterogeneities influence task-related BOLD signal in eloquent areas despite their apparent anatomical integrity but located close to an injured brain region.…”
Section: Krainik Et Al Impaired Vascular Reactivity and Bold Signal 1149mentioning
confidence: 99%